Historical investigation of medical treatment for adult congenital heart disease: A Canadian perspective. (19th November 2018) - Lapum, Jennifer L.; Fredericks, Suzanne; Bailey, Barbara; Yau, Terrence M.; Graham, Jennifer; Marelli, Ariane J.
Abstract: Objective: The number of adults with congenital heart disease (CHD) has increased substantially because of medical advances that are extending life expectancy beyond childhood. A historical investigation is timely not only because of this significant demographic shift, but also because stakeholder engagement is increasingly important in shaping research directions. The study questions were: From the perspective of stakeholders, what is known about the medical treatment for the adult CHD cohort in Canada and how has it changed over time? Design/Methods: We harnessed the use of historical research methods and conducted interviews with 21 key informants in order to articulate a contextualized understanding of the evolution of adult CHD treatment in Canada. The informants recruited were currently or previously located in and/or involved in treatment in seven provinces and two territories across Canada including patients, families, advocates, researchers, and practitioners located in disciplines that included cardiology, cardiovascular surgery, nursing, psychology, dietetics, and kinesiology. Results: Alongside findings that highlighted the significant demographic shift, the findings highlight key themes related to temporal shifts in treatment, emergence of organizational structures and use of evidence, comprehensive approaches to care, and future directions. A critical finding that requires immediate attention is the significantly disproportionate resources to the number of adults living with CHD, and as a result, the real risk of premature death for this population. Conclusions: The insights provided behoove the community of stakeholders to think creatively on how to draw attention to the inadequacy of resources and the unique and diverse needs of this population.